Antibacterial properties of experimentally produced birch tar and its medicinal affordances in the Pleistocene - Tjaark Siemssen; Aderonke Oludare; Marcel Schemmel; Janos Puschmann; Matthias Bierenstiel (PLoS ONE, 2026)
Birch tar is well-documented for its use as an adhesive in the Middle Palaeolithic of Europe, but other uses remain poorly explored. Drawing from recent arguments suggesting multimodal uses of products such as ochre and birch tar, this study tests the antibiotic properties of birch tar produced experimentally with methods reconstructed from Middle Palaeolithic birch tar finds from Europe. Made from the bark of Betula pendula and Betula pubescens, widely documented for the European Late Pleistocene, we produced birch tar samples using an underground pit method, a condensation method, and a modern tin can method. The birch tar samples were tested for antibiotic properties using the modified Kirby-Bauer disc diffusion antibiotic assay. The resulting inhibition zones, ranging from no effect to 10.5 ± 0.7 mm with a mean of 7.5 ± 0.17 mm, indicate a moderate effect against the Gram-positive Staphylococcus aureus , a bacterium widely known for its role in wound infections. We further establish that the efficacy of antibiotic properties is not related to the production method, with all methods showing a degree of variation. This supports a coevolutionary relationship between medicinal and technological use and production of birch tar during the Pleistocene. The antibiotic properties documented in this study are consistent with the use of birch tar as a wound dressing and skin ointment in Mi’kmaq communities in Eastern Canada, and the use of birch tar in Saami communities of Lapland. Arguing from an underexplored angle between experimental archaeology and ethnopharmacology, we suggest that similar to the ethnographic examples, a use of birch tar beyond exclusively technological contexts must be considered for the Middle Palaeolithic.